STUDI PERUBAHAN KARET ALAM (SIR-10) MENJADI KARET ALAM CAIR DAN KARET ALAM SIKLIS (CYCLIC NATURAL RUBBER) - Eddyanto -; Yuslina Wati Ardina (PROSIDING SEMINAR KIMIA, 2013)
The main aims of this work is to produce a lower molecular weight of cyclisised natural rubber (CNR) from chemically chain scission of natural rubber (SIR-10). By chemical modification of natural rubber, it is possible to modify its basic properties (for instance, improvement of solubility as a candidate to be a natural resin in an emulsion paint). The purpose of the present paper is to give an preliminary research to analyze the change of functional group by means of Fourier Transform Infrared (FTIR), especially dealing with natural rubber degradation and cyclisation products derived from the rubber (SIR-10) 1,4-polyisoprene. It was found that the cyclisation degree of cyclic natural rubber was 73%.